Comparative study of organic contaminants in agricultural soils at the archipelagos of the Macaronesia. (15th May 2022) - Acosta-Dacal, Andrea; Hernández-Marrero, María Eugenia; Rial-Berriel, Cristian; Díaz-Díaz, Ricardo; Bernal-Suárez, María del Mar; Zumbado, Manuel; Henríquez-Hernández, Luis Alberto; Boada, Luis D.; Luzardo, Octavio P.
Abstract: The occurrence of organic pollutants in soil is a major environmental concern. These compounds can reach the soil in different ways. Point sources, related to pesticides that are used intentionally, can be applied directly to the soil, or reach the soil indirectly due to application to the aerial parts of crops. On the other hand, non-point sources, which reach soils collaterally during irrigation and/or fertilization, or due to the proximity of plots to industrialized urban centers. Long-range transport of global organic pollutants must also be taken into account. In this study, 218 pesticides, 49 persistent organic pollutants, 37 pharmaceutical active compounds and 6 anticoagulant rodenticides were analyzed in 139 agricultural soil samples collected between 2018 and 2020 in the Macaronesia. This region comprised four inhabited archipelagos (Azores, Canary Islands, Cape Verde, and Madeira) for which agriculture is an important and traditional economic activity. To our knowledge, this is the first study on the levels of organic compound contamination of agricultural soils of the Macaronesia. As expected, the most frequently detected compounds were pesticides, mainly fungicides and insecticides. The Canary Islands presented the highest number of residues, with particularly high concentrations of DDT metabolites (p, p' DDE: 149.5 ± 473.4 ng g −1 ; p, p' DDD: 16.6 ± 35.6 ng g −1 ) and of the recently used pesticide fenbutatin oxide (302.1 ± 589.7 ng g −1 ). Cape Verde was the archipelago with the least contaminated soils. Very few pharmaceutical active compounds have been detected in all archipelagos (eprinomectin, fenbendazole, oxfendazole and sulfadiazine). These results highlight the need to promote soil monitoring programs and to establish maximum residue limits in soils, which currently do not exist at either continental or local level. Graphical abstract: Image 1 Highlights: The agricultural soils of the Canary Islands were the most contaminated. DDE is present in high levels in more than 70% samples in the Canaries. Cape Verde soils presented the lowest variety of residues, with only 17 compounds. All samples showed at least one residue, mainly fungicides and insecticides. The agricultural soils of the Macaronesia barely show any residues of PhACs.